Pomegranate (punica granatum): a comprehensive review of its medicinal properties and traditional uses and prospect in wellness industry - Anggraini, Putu Rahayu Natalia; Ciawi, Yenni (Jurnal Biologi Udayana; Vol 28 No 1 (2024): JURNAL BIOLOGI UDAYANA, 2024)
Pomegranate ( Punica granatum ) is a fruit-bearing shrub with a rich history of traditional use in various medicinal systems. This review paper aims to provide an in-depth analysis of the botanical profile, medicinal properties, and applications of pomegranate. Additionally, it explores its significance in traditional medicine systems, including Ayurveda, Chinese medicine, American Indian medicine, and the Usadha Taru Premana palm manuscript—a revered Balinese medicinal palm manuscript, and The Holy Quran. The review highlights the active compounds, therapeutic potential, regional variations, cultivation, culinary uses, and its emerging role in the tourism and wellness industry.